Assessing visitors' attitude and behaviour of visiting Melaka / Fauzunnasirah Fazil, Norfadhilah Mohd Akhuan and Shareenie Shera Abdul Hamid - Fazil, Fauzunnasirah; Mohd Akhuan, Norfadhilah; Abdul Hamid, Shareenie Shera (Research Management Institute (RMI), 2012)
Malacca is one of the most popular tourism destinations in Malaysia. It has developed over 500 years of trading and cultural exchanges between East and West in the Straits of Malacca. The states are more outstanding in the eyes of the world when Malacca and its fellow, Georgetown were listed in the UNESCO (United Nation United Nations Educational, Scientific and Cultural) World Heritage Cities List under "Historic Cities in the Straits of Malacca" on lx July 2008. Such listing implied Malacca is indirectly belongs to all the people of the world, irrespective of the territory on which they are located. Apparently, tourists from different parts of the world are bringing different attitudes and behavior depending on their psychological and social factors that may result positive or negative impact to the visited destinations. Every year government spent a lot of money to enhance cultural and heritage tourism activities in Malacca while tourism players are heavily promoting the destination to capture more tourists. However, are visitors visiting Malacca have proper attitudes to participate in sustainable tourism activities? Therefore, the aims of this study are (i) to identify the attitudes and travel behavior of visitors visiting Malacca and (ii) to indicate the effects of such attitudes towards visitors' behavior during visiting Malacca. Upon completion, it is hoped that this study may contribute a body of knowledge pertaining visitors' attitudes and behavior towards sustainable tourism development that support green tourism campaign currently done by the government. It aims to create awareness among tourism operators in Melaka in order to attract right people with right attitudes as to promote and conserve the Historical City of Malacca for its further popularization in the long run. Discovering visitors' attitudes and behavior may contribute ideas to tourism operators on how to attract right target market to visit and appreciate Malacca in right manner.